Teaching Skills of the Prospective Physical Education Teachers Based on Group Learning Commitment - Blegur, Jusuf; Lumba, Andreas J. F. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Microteaching focuses on student collaboration efforts to improve teaching skills. Teaching skills are essential for prospective teachers. However, problems still arise because all members are not committed to supporting teaching skills as the ultimate goal of micro-teaching learning. This study aimed to examine differences in the teaching skills of prospective physical education teachers based on group learning. Commitment. This study uses a comparative quantitative design method. The sample involved is 41 students who are programming micro-teaching courses. Skills data were collected using observation guidelines and group learning commitment data using the Organizational Commitment Scale. The techniques used for data analysis are qualitative descriptive analysis and quantitative and inferential statistics. The findings prove that those who commit to group learning have better teaching skills than those who have a low commitment to group learning. Commitment to group learning can help students acquire skills through creating a sense of comfort in learning, reflecting on a responsibility to improve themselves, and trying to help peers through the role of observer and reflection.